The Molecular Effects of Dietary Acid Load on Metabolic Disease (The Cellular PasaDoble: The Fast-Paced Dance of pH Regulation) - Williamson, Morgan; Moustaid-Moussa, Naima; Gollahon, Lauren (Frontiers in Molecular Medicine, 2021)
The NIH National Institute of Diabetes and Digestive and Kidney Disease (NIDDK) reported that 70% of the U.S. population is overweight or obese, 11% of the adult population has diabetes (Type 1 or 2), and 90% of diabetic patients are also overweight/obese (NIDDK, 2020). Both of these conditions are highly diet and lifestyle dependent, suggesting dietary intervention as a logical step towards battling this growing problem. Further investigation into these dietary-induced trends have resulted in key findings showing oxidative stress and metabolic acidosis as shared symptoms and pre-diagnostic tools for many related diseases such as chronic kidney disease, hypertension, cardiovascular disease, osteoporosis, and even cancers. Dietary analysis shows that a “modern” diet may facilitate a disruption in pH homeostasis and drive disease progression through high consumption of exogenous acids. Because so many physiological and cellular functions rely on acid-base reactions and equilibrium, prolonged exposure of the body to more acids than can effectively be buffered will result in metabolic stress followed by disease. This review addresses current, relevant molecular pathways in mammalian cells discovered to be sensitive to proton concentration and acid - base equilibria, and discuss how dietary changes may influence or re-establish pH homeostasis, potentially attenuating disease progression.